Pengaruh Customer Relationship Management Terhadap Kepuasan Pelanggan Pada Perusahaan UD Sarin Gumi - I Putu Krisna Widyasatrya Dhananjaya; Made Irma Dwiputranti; I Gusti Agung Prabandari Tri Putri (STMIK Banjarbaru, 2025)
This research discusses the effect of Customer Relationship Management (CRM) on customer satisfaction at UD Sarin Gumi, a company in the agricultural trade and distribution sector. The problem faced is the unclear effectiveness of CRM in increasing customer satisfaction. This study aims to measure the relationship of CRM, represented by indicators of commitment, communication and service quality, with customer satisfaction assessed based on product, price and service. The methodology used is descriptive quantitative approach with data collection through questionnaires with 51 respondents, analyzed using simple linear regression with Statistical Package for the Social Sciences (SPSS) version 26. The results showed that CRM has a significant influence on customer satisfaction, with a determination value of 68.2%, which confirms that most of the value of customer satisfaction is influenced by CRM. These results confirm that good CRM implementation can increase customer satisfaction and provide a strategic path for companies to strengthen customer relationships.Keywords: Customer Relationship Management; Customer Satisfaction; Statistical Package for the Social SciencesAbstrakPenelitian ini membahas mengenai pengaruh Customer Relationship Management (CRM) terhadap kepuasan pelanggan pada UD Sarin Gumi, perusahaan di sektor perdagangan dan distribusi pertanian. Masalah yang dihadapi adalah ketidakjelasan efektivitas CRM dalam meningkatkan kepuasan pelanggan. Penelitian ini bertujuan untuk mengukur hubungan CRM, yang diwakili oleh indicator komitmen, komunikasi dan kualitas layanan, dengan kepuasan pelanggan yagn dinilai berdasarkan produk, harga dan layanan. Metodologi yang digunakan adlaah pendeketana kuantitatif deskriptif dengan pengumpulan data melalui kuesioner dengan 51 responden, dianalisis menggunakan regresi linier sederhana dengan Statistical Package for the Social Sciences (SPSS) versi 26. Hasil penelitian menunjukkan bahwa CRM memiliki pengaruh signifikan terhadap kepuasan pelanggan, dengan nilai determinasi sebesar 68,2%, yang menegaskan bahwa Sebagian besar nilai kepuasan pelanggan dipengaruhi oleh CRM. Hasil ini menegaskan bahwa implementasi CRM yang baik dapat meningkatkan kepuasan pelanggan dan memberikan jalur strategis bagi perusahaan untuk memperkuat hubungan pelanggan.Kata kunci: Customer Relationship Management; Kepuasan pelanggan; Statistical Package for the Social Sciences